Efficacy of Daclatasvir with Sofosbuvir for Treating Chronic Hepatitis C Genotype 3 - Fahad Aman Khan, Mukhtar Ahmad, Imran Khan, Aniqa Anser Tufail Khan, Muhammad Kashif, Tashia Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine efficacy of Daclatasvir with sofosbuvir in treating patients of chronic hepatitis C genotype 3. Study Design: Interventional case-series study Place and Duration of Study: Hepatitis Clinic, Medical Unit–II, Jinnah Hospital, Lahore from January 2019 to June 2019. Methodology: One hundred and thirty five patients of chronic hepatitis C Genotype 3 were enrolled. All patients were givendaclatasvir60mg and sofosbuvir 400mg once-daily for 12 weeks. HCV-RNA-PCR was done at end of 12 weeks of treatment (ETR) and 12 weeks after end of treatment (SVR). Results: The mean age of the patients was 49.8 ±2.3 years. There were 57.7% males while 42.2% females with 22.2% frequency of cirrhosis in them.The mean value of AST and ALT was calculated as 57.07 ± 48.69 and 51.02 ± 44.17 IU/ml respectively in hepatitis C patients having genotype 3.The treatment follow up showed that on reassessing the hepatitis C status through quantitative analysis of genotype 3 through PCR it was seen that 91.1% patients reached SVR with no viral detection in them. Conclusion: Daclatasvir in combination to sofosbuvir is an efficient way of treating hepatitis C patients suffering from genotype 3.